Enhancing Energy Efficiency in HVAC With RFID Technology Based Occupancy Detection Solution - Suk, Joseph (Auckland University of Technology, 2017)
Over the years, the concept of smart buildings or intelligent buildings has been discussed and revealed as an effective solution to reduce the energy consumption of residential and commercial buildings without any impact on occupants’ thermal comfort. To optimize the building operation, the exact location of occupants inside buildings should be identified and devices such as RFID sensors used as an effective solution to increase the accuracy of an occupancy detection system. Until now, I have not find specific energy efficient solutions for heating or energy consumption but in this research I propose an accurate and power efficient approach to detect the occupants in an open office and a training room using mobile devices to send signals. This approach may experience the occupancy detection problem but resolves it by exploiting iBeacon which is a low-power technology. Along with the iBeacon technology, Bluetooth low energy (BLE) technology is used as it presents a very power efficient technology. iBeacon technology with BLE is a good solution for occupancy detection in buildings because of its higher level of compatibility and accurate detection.
Keywords: RFID; HVAC; Energy efficiency; Occupancy detection